Coccids (Hemiptera, Coccinea) and their natural enemies in the vineyards of Georgia: present situation (Bollettino di zoologia agraria e bachicoltura, 2024)
Several scale insects species are recorded in Georgian vineyards.Among them the mealybug, Planococcus ficus (Signoret), and the cottony scale,Neopulvinaria innumerabilis (Rathvon), are the most prevalent and serious pestsin the dry eastern regions. In the humid regions of the Black Sea coast themealybug Pseudococcus vibumi (Signoret) is an occasional noxious pest. Othercommon coccids, Parthenolecanium corni (Bouche), P. persicae (F.), andPulvinaria betulae L., are rare, minor pests in the vineyards and have no economicimportance. Two hymenopterous s pecies, Anagyrus pseudococci (Girault)(Chalcidoidea, Encyrtidae) and Allotropa mecrida (Walker) (Proctotrupoidea,Platygasteridae), are parasitoids of P. ficus. Some species of hyperparasitoids havealso been recorded, namely Pachyneuron muscarum (L.), Chartocerus subaeneus(Forster) and Marietta. picta (Andre). Currently, the key pest of vine in easternGeorgia is the cottony maple scale, where many outbreaks have occurred. Tb.isspecies of American origin (Canada, USA), spread in the Caucasus (Georgia,Armenia) and in some European countries (ijrance, Italy) without the naturalenemies that suppressed it in America. No effective natural enemies have beenfound in Georgia. Three chalcid parasitoids, known as parasitoids of local coccids,have been recorded on this pest: Coccophagus maculipennis Jasnosh (whosenatural host is Acanthopulvinaria orientalis (Nassonov)), C. palaeolecaniiJasnosh, and C. lycimnia Walker. The larvae of Leucopis alriceps (Czerny)(Diptera), Chrysopa spp. (Neuroptera) and Scymnus spp. (Coleoptera,Coccinellidae) have been recorded as predators. Breeding programs were initiatedmore than 50 years ago for tbe i1in-oduced coccu1ellid predator, C1yptolaemusmontrouzieri Mulsant, to conu·oJ coccids. In regions with drier climates, whereC. montrouzieri is less effective, a C. monrrouzieri strain introduced from Israelis being tested and preliminary experiments have found it to be more effective.In conclusion, indigenous natural enemies are not capable of reducing the impactof P. ficus and N. innumerabilis populations to non-economic levels. Developingeffective biocontrol of these pests will be essential.
Keywords: Vineyard,; scale insects; pests; natural enemies; economic importance